Tradition, Modernity, and Postmodernity in Arabic Literature : Essays in Honor of Professor Issa J. Boullata - Hallaq, Wael,; Abdel-Malek, Kamal, (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
The collection of essays contained in this volume is written by a group of prominent scholars of Arabic literature. They explore various manifestations of traditional as well as modern and postmodern themes and techniques in Arabic literature. This is the first time the tripartite concepts of tradition, modernity, and postmodernity in Arabic literary works are explored and analyzed in one volume. It illustrates very clearly the fact that Arabic literature has kept abreast not only of the primarily modern literary movements in the West - that is amply illustrated by many studies to date - but also of the "postmodern condition". Scholars in the fields of Arabic literature, Islamic Studies, Comparative Literature, postmodern studies, among others, will find this collection of essays of great interest.